BRINGING MEDICAL GENETICS TO THE PUBLIC: THE CHALLENGES FOR INDONESIAN MEDICAL FACULTIES - Sulistiyana, Catur Setiya (Proceedings of the International Conference on Applied Science and Health, 2019)
-